EXPLORE EMBROIDERY AND WEAVING TAPESTRY WITH SHIBORI TECHNIQUES ON OUTER READY TO WEAR CLOTHING - Fajar, Elina Almara; Falah, Asep Miftahul (CAIJ: Creative Arts Interdisciplinary Journal, 2022)
The discussion of this research is based on how to exploreembroidery techniques and tapestry weaving techniquesin ready-made garments with an exploration of shiboritechnique in the textiles to be used, so that they can providegreater value in educating fashion users to reduce theproblem of textile and fashion waste pollution. This studyuses an experimental method, namely a research methodthat explores processing and dyeing techniques for naturalfibers and uses the design thinking phase, which consists offive phases, namely Empathize, Define, Ideate, Prototype,Test. The research design used a t-test as an experimentaldesign. The data collection was done by literature study injournals, books, articles and internet. In this study, the designis limited by the use of natural fibers in the form of cottonfabric and the use of natural dyes (Secang and Jambal). Theproduct design is limited to wearable outerwear productsthat have a simple design but are still in line with currenttrends. The results of this study are fashion prototypesusing embroidery techniques and tapestry weaving with theshibori dyeing method applied to ready-to-wear outerwearusing natural fibers as cotton fabric material.Keywords: Fashion, Weaving, Tapestry, Shibori Technique,Ready To Wear